ANALISIS PENGARUH KEMISKINAN TERHADAP TINDAK KRIMINALITAS DI SUMATERA UTARA - Putri, mardia anita; Azansyah, Azansyah (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sumatera Utara, 2024)
This research aims to analyze the influence of poverty on crime in North Sumatra. The data used is secondary data which includes poverty levels and crime rates from several districts/cities in North Sumatra. The analytical method used is panel data regression to see the relationship between the independent variable,namely poverty, and the dependent variable, namely crime. The research results show that poverty has a positive influence on crime rates. The higher the poverty level, the higher the crime rate that occurs. Based on these results, it is recommended for the government to increase efforts to eradicate poverty. This research has limitations in the variables used and limited data coverage, so it is hoped that future research can add other variables and use wider data to obtain more comprehensive results.